2003
DOI: 10.1016/s0735-1097(02)02772-9
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves biventricular oxidative metabolism and left ventricular efficiency in patients with dilated cardiomyopathy

Abstract: Exercise training improves exercise tolerance and LV function. This is accompanied by a decrease in biventricular oxidative metabolism and enhanced forward work efficiency. Therefore, exercise training elicits an energetically favorable improvement in myocardial function and exercise tolerance in patients with DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 35 publications
6
57
0
2
Order By: Relevance
“…First, it has long been known that interventions that aim to increase ventricular systolic performance increase the risk of death in patients with heart failure, whereas energy‐sparing treatments, such as angiotensin‐converting enzyme inhibitors or beta‐blockers, improve prognosis in heart failure. It has been thought that exercise‐based cardiac rehabilitation might be an exception to this rule in patients with nonischemic heart failure, given that 2 previous studies showed significant improvements in LV mechanical efficiency in patients with dilated cardiomyopathy 36, 37. Our findings support and extend these findings to patients with systolic heart failure of ischemic origin, in whom efficient energy utilization is of greatest importance.…”
Section: Discussionsupporting
confidence: 85%
“…First, it has long been known that interventions that aim to increase ventricular systolic performance increase the risk of death in patients with heart failure, whereas energy‐sparing treatments, such as angiotensin‐converting enzyme inhibitors or beta‐blockers, improve prognosis in heart failure. It has been thought that exercise‐based cardiac rehabilitation might be an exception to this rule in patients with nonischemic heart failure, given that 2 previous studies showed significant improvements in LV mechanical efficiency in patients with dilated cardiomyopathy 36, 37. Our findings support and extend these findings to patients with systolic heart failure of ischemic origin, in whom efficient energy utilization is of greatest importance.…”
Section: Discussionsupporting
confidence: 85%
“…It has been thought that exercise-based cardiac rehabilitation might be an exception to this rule in patients with nonischemic heart failure, given that 2 previous studies showed significant improvements in LV mechanical efficiency in patients with dilated cardiomyopathy. 36,37 Our findings support and extend these findings to patients with systolic heart failure of ischemic origin, in whom efficient energy utilization is of greatest importance. Second, the change in neither VAC nor mechanical efficiency correlated with the change in peak VO 2 in our cohort.…”
Section: -14supporting
confidence: 80%
“…In addition, Ukkonen et al demonstrated in patients with congestive heart failure that higher oxidative metabolism in the right ventricle relative to that in the left ventricle was related to an increased ventilatory drive, reflected by the slope of increase of ventilation relative to carbon dioxide production, which in turn was associated with increased mortality in these patients (19). Therapeutic interventions for LV heart failure, such as exercise training in dilated cardiomyopathy patients, were shown to also have a positive effect on RV oxidative metabolism, with a significant reduction of RV K mono (20). Similarly, cardiac resynchronization therapy in patients with idiopathic dilated cardiomyopathy also enhanced RV oxidative metabolism and metabolic reserve during stress (21).…”
Section: Discussionmentioning
confidence: 99%